2016
DOI: 10.1118/1.4941739
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic fractal signature dissimilarity analysis for therapeutic response assessment using dynamic contrast‐enhanced MRI

Abstract: Purpose: To develop a dynamic fractal signature dissimilarity (FSD) method as a novel image texture analysis technique for the quantification of tumor heterogeneity information for better therapeutic response assessment with dynamic contrast-enhanced (DCE)-MRI. Methods: A small animal antiangiogenesis drug treatment experiment was used to demonstrate the proposed method. Sixteen LS-174T implanted mice were randomly assigned into treatment and control groups (n = 8/group). All mice received bevacizumab (treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 63 publications
(65 reference statements)
0
12
0
Order By: Relevance
“…They describe the heterogeneity of the tumor margin or shape (Appendix S1). [27][28][29][30] Using these features, we found two distinct tumor growth patterns that had specific margin-related radiomic features that were predictive of tumor DT. Our major findings were: (i) for all ADCs, the combination of eccentricity, surface-to-volume ratio, LoG uniformity (σ = 3.5), and LoG skewness (σ = 0.5) had predictive ability for tumor DT; (ii) the majority of subjects were assigned to the GP I group (n = 41) because they had gradually growing tumors without a temporary decrease in tumor volume, and the finally selected radiomic features for predicting tumor DT in this group were similar to those found for total subjects, namely surface-to-volume ratio, contrast, LoG uniformity (σ = 3.5), and LoG skewness (σ = 0.5).…”
Section: Discussionmentioning
confidence: 99%
“…They describe the heterogeneity of the tumor margin or shape (Appendix S1). [27][28][29][30] Using these features, we found two distinct tumor growth patterns that had specific margin-related radiomic features that were predictive of tumor DT. Our major findings were: (i) for all ADCs, the combination of eccentricity, surface-to-volume ratio, LoG uniformity (σ = 3.5), and LoG skewness (σ = 0.5) had predictive ability for tumor DT; (ii) the majority of subjects were assigned to the GP I group (n = 41) because they had gradually growing tumors without a temporary decrease in tumor volume, and the finally selected radiomic features for predicting tumor DT in this group were similar to those found for total subjects, namely surface-to-volume ratio, contrast, LoG uniformity (σ = 3.5), and LoG skewness (σ = 0.5).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that d 1 and d 2 of K trans map might reflect the tumor heterogeneity differences between low and high-grade glioma (Rose et al , 2009). In one of our recent works, the d 1 and d 2 of K trans map were found to be useful in determining the bevacizumab therapeutic effect (Wang et al , 2016). …”
Section: Methodsmentioning
confidence: 99%
“…Advantages of fractal dimension are that it is relatively stable, less susceptible to noise than other features, and can be used for longitudinal assessment in a single patient [32]. Another feature of interest is the recently developed fractal signature dissimilarity method, which has been suggested as a novel image texture analysis technique [33]. In that study, the fractal signature dissimilarity method was used to quantitatively assess contrast agent uptake heterogeneity dynamics, indicating a potential role in monitoring the early response to anti-angiogenesis treatment [33].…”
Section: ) Model-based Featuresmentioning
confidence: 99%